Stakeholders’ Perceptions of Seismic Risk and Adaptive Capacity to Earthquake: The Case of Anse-à-Veau (Haiti) - Garry Jourdan; Michelet Clerveau; Wisly Dieujuste; Sabine Henry (European Scientific Journal, ESJ, 2023)
Earthquakes were responsible for more than half of all natural disaster deaths worldwide between 2000 and 2019. Populations in developing countries are the most affected. What can help stakeholders to increase people adaptive capacity to earthquake in a context of very limited financial resources?The perception of seismic risk by the stakeholders and the perception of their adaptive capacity seemed to be able to influence the stakeholder’s adaptive capacity to earthquakes as well as that of the population. Haiti, a country at risk of earthquakes and ranked among the poorest in the world, is a relevant place to explore the potential people adaptive capacity to earthquake. Face-to-face interviews were conducted with 21 stakeholders in the Town of Anse-à-Veau, in 2020 to focus on their perceptions of risk and adaptive capacity, just one year before an earthquake in the region.Results show that stakeholders were mostly aware of earthquake risk. This was identified by their perception of seismic risk related to the zone and the perception of their adaptative capacity to deal with earthquakes. Respondents perceived some drivers such as self-capacity, motivation and self-responsibility can increase their adaptive capacity. Some temporal and physical factors have been highlighted as constraints to stakeholders’ adaptive capacity to earthquake.As expected, training, awareness, and appropriate constructions were identified as effective ways to increase the adaptive capacity of stakeholders and the one of the local populations to earthquakes. Surprisingly, earthquake unpredictability was seen as a barrier but also as a motivation for preparedness. Thus, this observation must be examined to find in which way it can facilitate adaptive capacity or not.Human resources are targeted as the main resource to cope with an earthquake. Also, training and awareness were recognized as means to increase stakeholders’ adaptive capacity and the one of the local populations to deal with such an event despite the limited financial resources.